Dasar Pertimbangan Hakim Menerapkan Sanksi Pidana Penjara Dan Pelatihan Kerja Dalam Perkara Narkotika Dengan Pelaku Anak - Khorisima Gusasih (Verstek, 2017)
This research aims to find out judgment of Judge of imprisonment and work training sanctions to Child on Narcotics Case already corresponding or not with KUHAP and Republic of Indonesia’s Act about Child Criminal Justice System.          This case arose from the defendant caught carrying a drug package containing marijuana , which she got from someone with an unknown number and than this package will be taken by others . This caused the defendant punishable by imprisonment and job training . This study aims to determine what are and how the consideration of judges in imposing sanctions of imprisonment and job training use Case Verdict Number : 02/Pid.Sus.Anak/2014/PN.Kng. Already corresponding or not with KUHAP and Republic of Indonesia’s Act about Child Criminal Justice System.          The conclusion of this study explain that in making the decision by the judge is in conformity with the reference to Article 183 KUHAP and Republic of Indonesia’s Act about Child Criminal Justice System with at least two items of evidence by Public Prosecutor in council which will create the instruction and legally proven guilty defendants violated Article 111 paragraph (1) of Republic of Indonesia’s Act Number 35 of 2009 about Narcotics, juridical facts, and non juridical facts, generate verdict of imprisonment verdict work training sanctions           Keywords : authentication, narcotics, decision.